Development and evaluation of a simple, multifactorial model based on landing performance to indicate injury risk in surfing athletes - Lundgren, L. E.; Tran, T. T.; Nimphius, S.; Raymond, E.; Secomb, J. L.; Farley, O. R. L.; Newton, R. U.; Steele, J. R.; Sheppard. J. M. (International Journal of Sports Physiology and Performance, 2015)
Purpose: To develop and evaluate a multifactorial model based on landing performance to estimate injury risk for surfing athletes. Methods: Five measures were collected from 78 competitive surfing athletes and used to create a model to serve as a screening tool for landing tasks and potential injury risk. In the second part of the study, the model was evaluated using junior surfing athletes (n = 32) with a longitudinal follow-up of their injuries over 26 wk. Two models were compared based on the collected data, and magnitude-based inferences were applied to determine the likelihood of differences between injured and noninjured groups. Results: The study resulted in a model based on 5 measures—ankle-dorsiflexion range of motion, isometric midthigh-pull lower-body strength, time to stabilization during a drop-and-stick (DS) landing, relative peak force during a DS landing, and frontal-plane DS-landing video analysis—for male and female professional surfers and male and female junior surfers. Evaluation of the model showed that a scaled probability score was more likely to detect injuries in junior surfing athletes and reported a correlation of r = .66, P = .001, with a model of equal variable importance. The injured (n = 7) surfers had a lower probability score (0.18 ± 0.16) than the noninjured group (n = 25, 0.36 ± 0.15), with 98% likelihood, Cohen d = 1.04. Conclusions: The proposed model seems sensitive and easy to implement and interpret. Further research is recommended to show full validity for potential adaptations for other sports.